Material Design Of English Textbook Bahasa Inggris SMA Kelas X To Develop Student's Communicative Competence Content Analysis - Retno Nursanti, Dyah, Prof. Dr Endang Fauziati, Ph. D. Mauly Halwat H (2016)
ABSTRACT DYAH RETNO NURSANTI, S20040024. "MATERIAL DESIGN OF ENGLISH TEXTBOOK BAHASA INGGRIS SMA KELAS X TO DEVELOP STUDENT'S COMMUNICATIVE COMPETENCE: CONTENT ANALYSIS". Muhammadiyah University of Surakarta. Thesis. 2016. This research focuses on analyzing the competencies covered in each tasks and activities in Bahasa Inggris SMA Kelas X textbook. The objectives are to explain what linguistic competence, strategic competence, socio-cultural competence, actional competence, and discourse competence are shown in the tasks of English textbook Bahasa Inggris SMA Kelas X, to elaborate frequency of communicative competence are shown in the tasks of English textbook Bahasa Inggris SMA Kelas X, and to elaborate the dominant communicative competence in the tasks of English textbook Bahasa Inggris SMA Kelas X. In achieving the objectives, the researcher uses descriptive qualitative as the type of the research. The data of this research was the tasks and activities of English textbook Bahasa Inggris SMA Kelas X. The data source of this research is Bahasa Inggris SMA Kelas X textbook published by Balitbang. In collecting the data the writer uses documentation. The technique for analyzing the data are classifying and describing the kinds of communicative competence, coding the data, scoring the data, counting the frequency and dominant of the competencies, and drawing conclusion. From the result of analysis, it can be drawn some conclusions. Firstly, from 104 data there are 40 or 38.4% the tasks which designed to develop student's linguistic competence, 6 or 5.8% the tasks which designed to develop student's strategic competence, 8 or 7.7% the tasks which designed to develop student's socio-cultural competence, 33 or 31.7% the tasks which designed to develop student's actional competence, 17 or 16.3% the tasks which designed to develop student's discourse competence. Secondly, the dominant of each Communicative Competence is Linguistic Competence. Thirdly, this textbook was sufficient because there only linguistic and actional competence which available tasks to develop its competence in 70%. Therefore, it can be conclude that Bahasa Inggris SMA Kelas X textbook is sufficient to develop student's communicative competence. Keywords: textbook, tasks, communicative competence